1989
DOI: 10.1590/s0102-311x1989000100007
|View full text |Cite
|
Sign up to set email alerts
|

Zoonoses: hospedeiros e reservatórios

Abstract: Em 1862, Thomas Huxley concluía um estudo sobre a Posição do Homem na Natureza, no qual procurava derrubar as barreiras conceituais e preconceituais que lhe atibuíam posição taxonômica privilegiada, imediatamente abaixo da dos anjos. Em 1877, Quatrefages, em seu livro sobre A Espécie Humana tentava, por outro lado, demonstrar que o homem merecia lugar de destaque na criação -e algumas raças, mais do que outras. Discordou de Lineu que, apesar de fixista, colocara-nos na mesma ordem dos macacos, e de Huxley que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…Rey (1992) suggested that the pathological nature of the parasitism is incidental, with the occurrence of the lesions not being constant with an energetic loss by the host. This apparent absence of impairment for the host can indicate a relationship between the anuran and the parasite that is a result of a long period of coevolution, with reciprocal adjustments and equilibrium (Cheng, 1964;Ávila-Pires, 1989). However, we must also consider that the host may be injured at physiological levels not detectable in the present study (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Rey (1992) suggested that the pathological nature of the parasitism is incidental, with the occurrence of the lesions not being constant with an energetic loss by the host. This apparent absence of impairment for the host can indicate a relationship between the anuran and the parasite that is a result of a long period of coevolution, with reciprocal adjustments and equilibrium (Cheng, 1964;Ávila-Pires, 1989). However, we must also consider that the host may be injured at physiological levels not detectable in the present study (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…A densidade destes animais está interligada a fatores sócio-econômicos, os quais são característicos e peculiares nos diferentes grupos populacionais (4) . Tem-se que considerar que a densidade populacional de cães não domiciliados varia de região para região, ou seja, quanto pior for a condição social de uma região, maior tende a ser a sua população de cães não domiciliados (40,41) . O ambiente também vai influenciar já que, quanto maior a possibilidade de abrigo, água e alimentos, maiores serão as condições de sobrevivência e, consequentemente, maiores as populações nas ruas (4) .…”
Section: Resultsunclassified
“…A zoonosis occurs when these conditions appear. But if the alteration is so great that the parasite becomes totally specific to the new host 9,90 , the outcome could be similar to HIV infection 76 . This may be McMICHAEL 80 argues that the historical transitions experienced by our prehistoric ancestors when they climbed down out of the trees onto the savannahs, incorporated meat into their diet, and more recently since the emergence of Homo sapiens, the development of agriculture, and the conquest of new territories and civilizations favored the emergence of (and exposure to) infectious agents of animal origin.…”
Section: Discussionmentioning
confidence: 99%